Evaluating the Unintended Health Consequences of Poverty Alleviation Strategies: Or What Is the Relevance of Mohammed Yunus to Public Health? - Mohindra, K. S. (Can J Public Health, 2008)
Public health researchers are increasingly shifting their attention away from merely documenting those factors that determine health–a solid evidence base on health determinants now exists–to improving our understanding of how various interventions influence population health. This paper argues for greater investigations of the potential unintended health benefits associated with participation in a poverty alleviation strategy (PAS) in low-income countries. We focus on microcredit, a PAS that has been spreading across the developing world. Microcredit aims to address the “credit gap” between the poor and the better off by offering an alternative for the poor to acquire loans: small groups are formed and loans are allocated to members based on group solidarity instead of formal collateral. We argue that microcredit corresponds with activities that will help build up health capital (e.g., greater access to resources) and describe the main pathways from microcredit participation to health. We advocate that microcredit and other potential pro-health PAS be included among the range of interventions considered by public health researchers in improving the health of the poor.